2018
DOI: 10.1016/j.forsciint.2018.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol production during autopsies: The risk of sawing in bone

Abstract: When sawing during autopsies on human remains, fine dust is produced, which consists of particles of sizes that may fall within the human respirable range, and can act as vectors for pathogens. The goal of this study was to explore the potential effects of saw blade frequency and saw blade contact load on the number and size of airborne bone particles produced. The methodology involved the use of an oscillating saw with variable saw blade frequencies and different saw blade contact loads on dry human femora. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
2
29
0
3
Order By: Relevance
“…Fourth, in these same cases, oscillating saws were not used, to comply with CDC recommendations and in line with studies showing that their use generates fine, respirable particles which may serve to deliver virus to the respiratory tract of personnel. 20 Fifth, in persons under investigation (swab-negative), the autopsy was targeted to structures of particular interest to avoid dispersion of potentially hazardous fluids around the morgue in the case of a false-negative result. Sixth, chest blocks, and lungs in particular, were perfused with 10% formalin prior to further examination (lung being further perfused via bronchi after removal with formalin in a steel pan).…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, in these same cases, oscillating saws were not used, to comply with CDC recommendations and in line with studies showing that their use generates fine, respirable particles which may serve to deliver virus to the respiratory tract of personnel. 20 Fifth, in persons under investigation (swab-negative), the autopsy was targeted to structures of particular interest to avoid dispersion of potentially hazardous fluids around the morgue in the case of a false-negative result. Sixth, chest blocks, and lungs in particular, were perfused with 10% formalin prior to further examination (lung being further perfused via bronchi after removal with formalin in a steel pan).…”
Section: Resultsmentioning
confidence: 99%
“…As another step to minimize the generation of aerosols, we tried to use the power saw at the lower frequency and to maintain the saw blade contact load to a maximum level. Pluim JME et al reported that higher saw frequency and low saw blade contact load led to higher production of aerosols [25]. Judicial use of an electrocautery (lower effective power, used with suction device to minimize the surgical smoke) and use of feeding tube as irrigation and suction cannula in place of pulse lavage system were others steps to minimize the production of aerosols during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A prior pilot study was performed on the influence of saw blade frequency and saw blade contact load on the production of aerosol in dry bone [12]. For the current study three additional parameters were selected that closely represent the variety in sawing parameters faced in daily practice.…”
Section: Methodsmentioning
confidence: 99%
“…Effects were considered significant when p ≤ 0.05. A more detailed description of the methodology can be found in our previously published research [14].…”
Section: Methodsmentioning
confidence: 99%